Kvantna mehanika potenciala xna-2 - Geršak, Rok (Matrika, 2017)
This article will search for eigenstates of the ?$x^{-2}$? potential. Three dimensional analog of this potential would represent an electric field of dipoles as in movement of an electron, which is attached to a closed-shell polar molecule. In general, every attractive potential allows scattering states and discrete bound states. This is true for potential well, delta function, harmonic oscillator and Coulomb potential. Careful readers should have noticed that ?$x^{-2}$? potential is missing in previous sentence, since it violates fundamental principles of quantum mechanics. To find any eigenstate of the ?$x^{-2}$? potential more sophisticated methods such as renormalization and self-adjoint extension need to be used.
Keywords: kvantna mehanika; potenciali; potentials; quantum mechanics; renormalizacija; renormalization; sebi adjungirana razširitev; self-adjoint extension